PENERAPAN ASAS LEX POSTERIORI DEROGAT LEGI PRIORI TERHADAP ANAK KORBAN PENCABULAN (STUDI KASUS PENGADILAN NEGERI JAKARTA UTARA NOMOR 195/Pid.Sus/2015/PN.Jkt.Utr) - Wendi .; Firman Wijaya (Jurnal Hukum Adigama, 2018)
Abuses against Children are included in Extraordinary Crimes and often occue mainly to minors. This is due to the lack of government in acting on the case. In this case, it occurred in a 3 years old boy who is abused by his own teacher.  Precisely happened on April 29, 2014 at Saint Monica Sunter during the dance extracurricular activity. The victim’s mother found out about it when the victim complained of pain in the part of his penis after the victim was abused. At that moment the victim’s mother reported the incident of abuse to the authorities. It was then estabilished that the defendant was guilty of fulfilling the elements of an offense against the victim. So the defendant must be held in the prison until the court process is decided. In the indictment given by the public Prosecutor charged with using Article 82 of Law Number 23 year 2002 on Child Protection. However, the Prosecutors should be using the updated Law which is Article 82 of Law Number 35 year 2014 on the protection of new Children in the Prosecution. This proves that the Prosecutor is less careful in preparing the indictment given so as to cause legal irregularities that should in decideng the case reflects the legal objectives of Justice, certainty and expediency. Where as in legislation known as the principle of lex posteriori derogat legi priori that should be in the case of obscenity this principle is enforced. Because in the  new Child protection Law more confirms the perpetrator of abuse if it is proven to commit abuse then the punishment is heavier that the old Law, and more to give special protection guarantee to the victim of abuse so that its rights will not be violated.